2012
DOI: 10.1097/aln.0b013e318260de41
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Peripheral versus  Central Coadministration of QX-314 and Capsaicin on Neuropathic Pain in Rats

Abstract: Background Neuropathic pain is common and difficult to treat. Recently a technique was developed to selectively inhibit nociceptive inputs by simultaneously applying two drugs: capsaicin, a transient receptor potential vanilloid receptor 1 channel activator and QX-314, a lidocaine derivative that intracellularly blocks sodium channels. We used this technique to investigate whether transient receptor potential vanilloid receptor 1-expressing nociceptors contribute to neuropathic pain. Methods The rat chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 95 publications
1
17
0
Order By: Relevance
“…Once inside, QX-314 is able to bind to the acting site on sodium channels. Shen et al [118] reported that the peripheral block of nociceptive afferents by QX-314 combined with capsaicin was effective in reducing neuropathic pain. It was also suggested that capsaicin could be applied in combination with bupivacaine and lidocaine instead of QX-314 [119].…”
Section: Anesthetic and Phytochemical Membrane Interactionmentioning
confidence: 99%
“…Once inside, QX-314 is able to bind to the acting site on sodium channels. Shen et al [118] reported that the peripheral block of nociceptive afferents by QX-314 combined with capsaicin was effective in reducing neuropathic pain. It was also suggested that capsaicin could be applied in combination with bupivacaine and lidocaine instead of QX-314 [119].…”
Section: Anesthetic and Phytochemical Membrane Interactionmentioning
confidence: 99%
“…Furthermore, it was revealed that QX-314 did not produce any effects on motor fiber function by itself, but it slightly prolonged the effect of lidocaine in agreement with the earlier behavioral studies, which described a potentiated motor paralysis after perisciatic co-administrations of QX-314 with bupivacaine or lidocaine (Binshtok et al, 2009;Brenneis et al, 2014;Roberson et al, 2011). As it was mentioned in the Introduction, QX-314 can produce selective inactivation of VGSCs in sensory neurons by entering the cells through TRPV channels (expressed only in the sensory fibers), therefore, its topical administration alone does not influence the motor functions (Binshtok et al, 2007;Binshtok et al, 2009;Kim et al, 2010;Shen et al, 2012). Until now only one study has recorded the EMG activity from the digastric muscle to painful stimuli of the dental cavity after QX-314 (and/or capsaicin) administration (Kim et al, 2010).…”
Section: Local Anestheticssupporting
confidence: 87%
“…Each rat was placed in a box (22 × 12 × 12 cm) containing a smooth glass floor ( Stoelting, Wood Dale, IL, USA )6266. The temperature of the glass was measured and maintained at 27 °C ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%